The prohibition of riba (interest) - Hosein, Imran Nazar; One Islam Productions (N.S.W, Australia : One Islam Productions, 2006)
Riba is usury. Usury is commonly understood as the lending of money at illegally high rates of interest. But riba, or usury, in Islam is the lending of money on interest, regardless of the rate of interest. This lecturer talk on riba in Islam
Title from title screen
Presenter : Sheikh Imran Hosein
DVD format
Keywords: Interest (Islamic law); Islamic law; Islam and economics